Risk Factors for Intensive Care Unit Admission in Patients with Autoimmune Encephalitis - Harutyunyan, Gayane; Hauer, Larissa; Dünser, Martin W.; Moser, Tobias; Pikija, Slaven; Leitinger, Markus; Novak, Helmut F.; Aichhorn, Wolfgang; Trinka, Eugen; Sellner, Johann (Frontiers in Immunology, 2017)
Background Prevention and early recognition of critical illness in patients with autoimmune encephalitis (AE) is essential to achieve better outcome. Aim of the study To evaluate risk factors for intensive care unit (ICU) admission and its prognostic impact in patients with AE. Patients and methods A reclassification of patients hospitalized between 2011 and 2016 revealed 17 “definite” and 15 “probable” AE cases. Thirteen patients (41%) developed critical illness and required ICU admission. The underlying conditions were intractable seizures or status epilepticus (54%), altered mental state (39%), and respiratory failure (8%). Results ICU admission was associated with longer time from first symptoms to hospitalization (p = 0.046). Regression analysis revealed that anemia on hospital admission and definite diagnosis of AE was associated with a higher risk of acquiring critical illness. At last follow-up after a median of 31 months (range 2.5–52.4), seven patients had died (23%) and 63% had a good outcome [modified Rankin Scale (mRS) 0–3]. Anemia was associated with poor prognosis (p = 0.021), whereas development of critical illness did not impact mortality and functional outcome. Conclusion We confirmed the need for ICU care in a subgroup of patients and the prevailing objective is improved seizure control, and definite diagnosis of AE and anemia were identified as risk factors for development of critical illness. However, prognosis was not affected by ICU admission.